Educational Technology : A Primer for the 21st Century - Huang, Ronghuai; Spector, J. Michael; Yang, Junfeng (Singapore : Springer Nature, 2019)
The aim of this book is to prepare students with knowledge and skills to understand the organizational needs and requirements of educational technology. Students should be able to use and manage both existing and emerging technologies effectively and be able to apply associated pedagogies to suit the environment, but also evaluate and manage technological advances of future and the requisite pedagogical shifts to achieve efficiency and effectiveness. The demand of educational technology has been rising steadily, primarily due to the fact that e-learning is a huge and significantly expanding world-wide industry. Commercial e-learning companies, training departments in large companies and organizations, computer software companies and educational institutions the world over employ large numbers of educational technology specialists. There is a strong demand for technologists who understand educational theories and for instructional designers and teachers who understand technologies. This book is targeted towards those who are looking for career in educational technology, instructional design, or media and information systems, or may want to continue their studies in graduate programs in learning and instructional technology, and those who are interested in becoming teacher in K-12 setting but need background in educational technology. This book will also act as a valuable resource in teacher education programs where primary focus on mainstream education and requires an authentic resource in instructional design and educational technology. Keeping in mind the varied needs of the organizations, employees and potential students, this book adopts a competency approach to learning and assessment. The themes and topics take a multi-disciplinary approach, and are aimed at preparing students for competent and innovative educational technology professionals.
Section 1 Introduction and overview -- Introduction to educational technology -- Introduction to learning in context of existing and emerging technologies -- Foundations, evolution and developments in educational technology -- Section 2 Perspectives -- Typologies and key approaches to educational technology -- Systems' perspectives of educational technology -- Users' Perspectives of educational technology -- Learner Experiences and Perspectives of Educational Technology -- Section 3 -- Design, implementation and evaluation -- Design requirements -- Design process and development lifecycles -- Instructional design and development -- Evaluation models, approaches and practices -- Section 4 Emerging technologies and advance applications -- Critical Issues in educational technology -- Emerging Issues in educational technology.
Purchased from Library Budget
Keywords: Educational technology; Education -- Data processing; Educational Technology; Computers and Education